THE INFLUENCE OF ORGANIZATIONAL CULTURE, LEADERSHIP, PERSONALITY AND MOTIVATION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF ESSELON III EMPLOYEES - E ANDEN , TRECY (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2021)
The purpose of this study was to determine the effect of organizational culture, leadership, personality, and motivation toward organizational citizenship behavior of the personnel echelon III the government Palangka Raya municipality. This research tried to answer problems about organizational culture with evidence of increasing service of the personnel echelon III. The research was conducted on organizational citizenship behavior personnel echelon III the government Palangka Raya, involving of 125 personnel echelon III that had been selected from the target populations of 156 personnel echelon III by using a quantitative approach with path analysis methods. the research of hypothesis testing showed: (1) organizational culture had a positive direct effect on OCB; (2) personality had a positive direct effect on OCB; (3) motivation had a positive direct effect on OCB; (4) organizational culture had a positive direct effect on motivation: (5) leadership had a positive direct effect on motivation; (6) personality had a positive direct effect on motivation. To improve the OCB personnel echelon III the government Palangka Raya needs to increase organizational culture, leadership, personality, and motivation.